Effects of organic pollution on biological communities of marine biofilm on hard substrata. (June 2015) - Sanz-Lázaro, C.; Fodelianakis, S.; Guerrero-Meseguer, L.; Marín, A.; Karakassis, I.
Abstract: We examined the effect of organic enrichment on diatom and bacterial assemblages of marine epilithic biofilms on two locations in the Mediterranean, one situated in Spain and the other in Greece. Total organic carbon, total organic nitrogen, stable isotopes (δ 13 C and δ 15 N) and chlorophyll a indicated significant incorporation of organic wastes, increased primary production and trophic niche modifications on the biofilms close to the organic enrichment source. In Spain, where the organic load was higher than in Greece, diatom and, to some extent, bacterial assemblages varied following the organic enrichment gradient. The taxonomic richness of diatom and bacterial communities was not influenced by organic enrichment. Classical community parameters showed consistent patterns to organic pollution in both locations, whereas community assemblages were only influenced when organic pollution was greatest. The successional patterns of these communities were similar to other epilithic communities. The modification of community assemblages induced by organic pollution may affect ecological functions. Highlights: We examined the effect of organic enrichment on assemblages of marine biofilms. Classical community parameters showed consistent patterns to organic pollution. Diatom and bacterial assemblages were affected under high level of organic enrichment. Successional patterns were similar to other communities inhabiting hard substrata. Assemblage modifications induced by organic pollution may affect ecological functions. Abstract : Organic pollution modifies the assemblages of biofilm communities which may affect important ecological functions.